Yin-Yang Mechanisms Regulating Lipid Peroxidation of Docosahexaenoic Acid and Arachidonic Acid in the Central Nervous System - Yang, Bo; Fritsche, Kevin L.; Beversdorf, David Q.; Gu, Zezong; Lee, James C.; Folk, William R.; Greenlief, C. Michael; Sun, Grace Y. (Frontiers in Neurology, 2019)
Phospholipids in the central nervous system (CNS) are rich in polyunsaturated fatty acids (PUFAs), particularly arachidonic acid (ARA) and docosahexaenoic acid (DHA). Besides providing physical properties to cell membranes, these PUFAs are metabolically active and undergo turnover through the “deacylation-reacylation (Land’s) cycle”. Recent studies suggest a Yin-Yang mechanism for metabolism of ARA and DHA, largely due to different phospholipases A2 (PLA2s) mediating their release. ARA and DHA are substrates of cyclooxygenases and lipoxygenases resulting in an array of lipid mediators, which are pro-inflammatory and pro-resolving. The PUFAs are susceptible to peroxidation by oxygen free radicals, resulting in the production of 4-hydroxynonenal (4-HNE) from ARA and 4-hydroxyhexenal (4-HHE) from DHA. These alkenal electrophiles are reactive and capable of forming adducts with proteins, phospholipids and nucleic acids. The perceived cytotoxic and hormetic effects of these hydroxyl-alkenals have impacted cell signaling pathways, glucose metabolism and mitochondrial functions in chronic and inflammatory diseases. Due to the high levels of DHA and ARA in brain phospholipids, this review is aimed at providing information on the Yin-Yang mechanisms for regulating these PUFAs and their lipid peroxidation products in the CNS, and implications of their roles in neurological disorders.